The neurologists : A history of a medical specialty in modern Britain, c.1789-2000 - Casper, Stephen T. (Book collections on Project MUSE., 2014)
Describes how Victorian physicians located in a medical culture that privileged general knowledge over narrow specialism came to be transformed into the specialised physicians we now call neurologists.